Heritage housing and the cuban legal system: A city case study - Baby Ramírez, Yousy (2025)
Heritage properties gain relevance every day due to the history and culture they treasure. Currently, a large part of the built heritage presents serious problems of deterioration, mainly in housing. The objective of this research is to identify the main deficiencies that exist in the legal regulation for the conservation of heritage homes in Cuban administrative legislation. The study is based on the analysis and synthesis method and qualitative technical (interviews, surveys and scientific observation). Revealing as results the main deficiencies that exist in the Cuban legal regulation for the conservation of heritage housing and thus facilitate the actions of legal operators. As conclusions it is maintained that the legal regulation for the conservation of heritage homes in Cuba over the years has acquired maturity and scope action of action. Cuban Criminal Legislation in its title V includes the protection of heritage homes.